FEN BİLGİSİ ÖĞRETMEN ADAYLARININ BİLİMSEL, TEKNOLOJİK VE TOPLUMSAL GELİŞİM ÖZEL ALAN YETERLİKLERİNE YÖNELİK ÖLÇEK GELİŞTİRME ÇALIŞMASI. - SARIŞAN TUNGAÇ, Aslı (Journal of International Social Research / Uluslararası Sosyal Araştırmalar Dergisi, 2016)
With the adoption of constructivist system, in the process of adaptation to changes on Science program, Ministry of Education published booklets about "Specific Area Competence" for every individual branch education. This study aims to develop a scale which attempts to measure "Scientific, Technological and Societal Development" which is one of the subscales of Science and Technology teacher's specific area competences. In this context, by making use of Science and Technology Teacher specific area competences booklet published by National Ministry of Education, we created an item pool which includes 64 items. The pilot practice form has been applied to 300 teacher candidates and data gathered from this application have been analyzed with explanatory factor analysis. In direction with result of explanatory factor analysis, some items were excluded and the final form appeared as having 23 items with 7 factors. Also, at the result of confirmatory factor analysis which has been done on data gathered from 300 samples, convenience of factor structures which have been determined with explanatory factor analysis has been shown. These seven factors are named as "Special Education Competence", "Scientific Process Competence", "Critical Thinking Competence", "Organizing Out-of- School Activity Competence", "Taking Security Precautions Competence", "Problem Solving Competence" and "Nature of Science Competence" and reliability of each factor has been respectively found as .652, .649, .549, .702, .517, .604, and .791. The reliability coefficient (Cronbach's Alpha) of Scientific, Technological and Societal Development Specific Area Competences (STSDAC) scale has been found as ,87.